Why Are Bidder Termination Provisions Included in Takeovers? - Chen, Zhiyao; Mahmudi, Hamed; Virani, Aazam; Zhao, Xiaofei (Journal of Financial and Quantitative Analysis, 2022)
Abstract We present a rationale for bidder termination provisions that considers their effect on bidders’ and targets’ joint takeover gains. The provision’s inclusion can create value by enabling termination when the target becomes less valuable to the bidder than on its own, but creates a trade-off because termination may also occur when the target is more valuable to the bidder than on its own. This trade-off explains why the provision is included in only some deals, and explains variation in termination fees. Inclusion of the provision is associated with larger combined announcement returns, provided that the termination fee is priced appropriately.